Enhanced localized and uniform corrosion resistances of bulk nanocrystalline 304 stainless steel in high-concentration hydrochloric acid solutions at room temperature. Issue 12 (December 2018) - Wang, S.G.; Sun, M.; Xu, Y.H.; Long, K.; Zhang, Z.D.
Graphical abstract: Abstract: The localized and uniform corrosion resistances of bulk nanocrystalline 304 stainless steel (NC-304SS) produced by severe rolling technique, and its conventional polycrystalline 304 stainless steel (CC-304SS) counterpart, were investigated in high-concentration hydrochloric acid solutions at room temperature. NC-304SS can scarcely suffer from localized corrosion in 4 mol/L and 5 mol/L HCl solutions during 5-day immersion tests, and in 1–3 mol/L HCl solutions during thirty-five-day immersion tests. The corrosion rate of NC-304SS was also less than that of CC-304SS during these immersion tests. The improved localized and uniform corrosion resistances of NC-304SS were explained in terms of the adsorption and chemical activity of Cl − on NC-304SS and CC-304SS characterized by X-ray photoelectron spectroscopy, and the valence electron configurations of NC-304SS and CC-304SS were characterized by ultra-violet photoelectron spectroscopy rather than conventional electrochemical results.